Elderly Community Participation in the ILP Posyandu Program in Talawi Mudiak Village, Talawi Subdistrict - Mayako, Puja Afwanda (Jurnal EL-RIYASAH, 2025)
This study aims to examine the participation of elderly residents in the Integrated Primary Health Services (ILP) Posyandu program at Simaung Indah ILP Posyandu, Talawi Mudiak Village, Talawi District. The ILP Posyandu is a government initiative designed to bring healthcare services closer to all stages of life. This research uses a descriptive method with a qualitative approach. The findings show that elderly participation in the ILP Posyandu activities remains low, mainly due to several factors: lack of information about the event schedule, changes in the service system that merge child, adult, and elderly services into a single session, and the elderly’s work commitments. Low attendance is also influenced by dissatisfaction with the new service system, such as the unavailability of medication on-site and an environment considered less comfortable for elderly individuals. To address these issues, Wilcox’s participation theory is applied, including steps such as improving information dissemination, direct consultation with the elderly, joint decision-making, collaboration in implementation, and providing ongoing support and motivation to participants. Through these strategies, it is hoped that elderly participation in the ILP Posyandu program can be increased, leading to better health monitoring among the elderly population in the area.